(untitled) (Research, Society and Development, 2020)
Introduction: During graduation, university students are exposed to mental health problems, due to aspects related to their social networks and the social support. In this context, there is a need for studies that explore this theme. Objective: to identify scientific production on social networks and social support in university students. Method: This is an integrative literature review, which consisted of searching for studies published in the last five years, in five international databases. Results: After the selection process, 42 studies were included. It is noteworthy that the family, especially the mother, and friends, were the main supporters mentioned. University students between 19 and 21 years of age had the lowest score for social support. In general, social support is associated with positive effects on the health of university students and insufficient social support linked to negative effects. Positive associations have been reported with empathy, intrinsic motivation to study, subjective and spiritual well-being, emotional intelligence, academic performance, life satisfaction, academic success, work / life balance, problem solving skills, among other factors. In contrast, insufficient social support was associated with stress, depression, loneliness, anxiety, drug use, fear of gaining weight, mental disorders, among other negative conditions. Conclusion: social networks can serve as social support throughout life, standing out in periods of transformations, changes and adaptive processes, such as those experienced during the period of academic training, representing a theme of worldwide interest.